1993
DOI: 10.1063/1.355183
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial reactions on annealing Cu/Al multilayer thin films

Abstract: Thin film reactions of Cu/Al multilayer films were investigated by differential scanning calorimetry and transmission electron microscopy. Sequential intermetallic compound formation was found in the temperature range from 300 to 620 K. With excess copper present in the as-deposited trilayer and multilayer films, the observed sequence was CuAl2 and Cu9Al4, and the interfacial reactions were controlled by interfacial and grain boundary diffusion. The activation energies for the formation of CuAl2 and Cu9Al4 are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 16 publications
3
28
2
Order By: Relevance
“…The formation of interfacial phases is affected by their energies of formation. According to previous study, 18) the formation energies of Al 4 Cu 9 and Al 2 Cu are 0.83 eV and 0.78 eV, and there is a greater diffusivity of Cu in Al than that of Al in Cu. Thus the first reaction product Al 2 Cu is presumed, and then the next reaction phase is Al 4 Cu 9 .…”
Section: Development Of Interfacial Phasesmentioning
confidence: 99%
“…The formation of interfacial phases is affected by their energies of formation. According to previous study, 18) the formation energies of Al 4 Cu 9 and Al 2 Cu are 0.83 eV and 0.78 eV, and there is a greater diffusivity of Cu in Al than that of Al in Cu. Thus the first reaction product Al 2 Cu is presumed, and then the next reaction phase is Al 4 Cu 9 .…”
Section: Development Of Interfacial Phasesmentioning
confidence: 99%
“…The formation of the interfacial phases is affected by their formation energies. According to a previous study, 18) the formation energies of Al 4 Cu 9 and Al 2 Cu are 0.83 eV and Figure 8 shows hardness value (HV) of different intermetallics for Al/Cu bimetal sheet annealed at 500 C for 180 min. Those intermetallics generally possess higher hardness values than those of corresponding base metals of aluminum and copper.…”
Section: Interface Structure Of Al/cu Bimetal Sheetmentioning
confidence: 99%
“…Previous studies indicated that Al 2 Cu and Al 4 Cu 9 were the first two IMC phases formed at the Al-Cu interface. [14,15,33] In a study of phase development for the Al-Cu system, Jiang et al [33] reported that the formation energies of Al 2 Cu and Al 4 Cu 9 phases were 0.78 and 0.83 eV, respectively. Because Cu diffuses faster than Al and the solid solubility of Cu in Al is very low (~0.33 at.…”
Section: A Microstructure Evolution During Fswmentioning
confidence: 99%